Methods of diagnosis of hip dysplasia in dogs - Lyubchenko Elena (EDP Sciences, 2021)
To diagnose hip dysplasia, you can use a test system, the essence of which is to create a subhabitation in the hip joint of the dog, laid on the side, while there is a click in the joint, which means that the test is positive, while the pressure on the knee joint of the hip joint does not happen. The most common method of diagnosing dysplasia worldwide is X-ray, in which the age of the dogs studied should be more than a year, and large and giant breeds are studied in the range of one to one and a half years, with the animal laid on the back so that the X-ray image shows the pelvis with the wings of the iliac bone and femurs, including the knee joints, therefore, it is also necessary to use sedation, which allows you to comply with all the requirements for styling. The resulting X-rays are assessed according to the main Xray characteristics of the hip joint, taking measurements on six parameters presented in the text of this article, and determining the type of dysplasia. Computed tomography and magnetic resonance imaging can reveal the instability of the pathology in the hip joint and improve understanding of the disease process.